Diversity of Oral Microbiome of Women From Urban and Rural Areas of Indonesia: A Pilot Study - Widyarman, Armelia Sari; Theodorea, Citra Fragrantia; Udawatte, Nadeeka S.; Drestia, Aradhea Monica; Bachtiar, Endang W.; Astoeti, Tri Erri; Bachtiar, Boy M. (Frontiers in Oral Health, 2021)
Objective:The studies on the influence of geographical and socio-economic factors on oral microbiome remain underrepresented. Indonesia Basic Health Research 2018, showed an increasing trend in non-communicable diseases compared to the previous report in 2013. The prevalence of diabetes, heart disease, hypertension and obesity reported to be higher in urban area than in rural area. Interestingly, the non-communicable diseases found to be more prevalent in females than males. The aim of this pilot study was to examine the oral health and oral microbiome derived from tongue samples of healthy Indonesian women from urban and rural areas. Methods:Twenty women aged 21-47 years old from DKI Jakarta’s residents (n=10) as representative of urban area, and Ende, Nangapanda, East Nusa Tenggara’s residents (n=10) as representative of rural area were recruited for this pilot study. The participants were evaluated by the Simplified Oral Hygiene Index (OHI-S) according to the criteria of Greene & Vermillion and divided into three groups. High-throughput DNA sequencing was performed on an Illumina iSeq-100 platform. Results:The principal component analysis displayed a marked difference in the bacterial community profiles between urban and rural localities. Presence of manifest was associated with increased diversity and an altered oral bacterial community profile in urban women. Two bacterial taxa present at significantly higher levels (adjusted p-value<0.01) found in urban oral microflora (Genus Prevotella and Leptotricia) could account for this difference irrespective of individual oral hygiene status. Linear discriminant analysis effect size (LEfSe) analysis revealed several distinct urban biomarkers. At species level, Leptotrichia wadei, Prevotella melaninogenica, Prevotella jejuni and Prevotella histicola, show excellent discriminatory potential for distinguishing oral microflora between urban and rural area. Further, using SparCC co-occurrence network analysis, patterns in dominant core oral microbiome assembly observed to be specific to its ecological niche between two populations. Conclusions:This is the first pilot study demonstrating oral microbiome characterization in Indonesian women in urban and rural area. We found that oral microbiome in women displays distinct patterns consistent with geographic locality and oral-hygiene status. The specific characterization of Indonesian women's microbiota is likely linked to geographical specific dietary habits, cultural habits, and socio-economic status or the population studied.